Resolusi RESOLUSI KONTROVERSI HUKUM BUNGA BANK DALAM PANDANGAN MUI, NU, DAN MUHAMMADIYAH - Samheri; Sofrotul Kamaliyah; Mahmudi, Mohammad; Khairul Jannah (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
In the context of Islamic Economics, Usury is a major sin. However, in the practice of usury, many people are still confused about the practice of usury in everyday life. Both usury in buying and selling and muamalah. Especially those related to bank interest. Because in sharia banking it has become a word that is widely known to both Muslims and non-Muslims. Where sharia banking provides the best service to its customers without usury or interest which is forbidden by Allah and is clearly written in the Koran and Hadith. But even though it has been clearly explained that usury activities are prohibited, it is still a matter of debate to this day. Therefore, this research aims to re-examine the meaning of usury in the Koran, as well as bank interest in the views of several scholars'.